The effect of epilepsy awareness on attitudes toward individuals with epilepsy in Turkish society: A case study from Northern Turkey - Fatma Gündüz Oruç; Gülden Atan (Epilepsia Open)
Abstract Objective The aim of this study ws to examine the level of knowledge (awareness) about epilepsy in Turkish society and its impact on attitudes toward individuals with epilepsy. Methods The study was designed as a descriptive and cross‐sectional research. The sample consisted of individuals aged 18–70 (n = 563) in a city in northern Turkey, surveyed between January and June 2024. Data were collected using a Personal Information Form, an Epilepsy Knowledge Scale (EKS), and a Public Attitudes Toward Epilepsy Scale (PATE). Simple linear regression analysis was employed to determine the effect of knowledge on attitudes. Results Participants' knowledge level was found to be moderate at 48.2%, while their negative attitude levels were low at 27%. It was determined that the level of knowledge about epilepsy has a significant negative effect on attitudes (F[1, 561] = 123.461; p < 0.001), with an explanatory rate (R2) of 0.180. Significance The study identified a moderate level of knowledge and a low level of negative attitudes toward epilepsy in Turkish society. Furthermore, as the level of knowledge increased, negative attitudes toward individuals with epilepsy decreased. Plain Language Summary The study found that individuals in Turkish society have a moderate level of knowledge about people with epilepsy (PWE). It was determined that their negative attitudes are at a low level. As the level of knowledge about epilepsy increases in Turkish society, it was observed that the negative attitude toward PWE decreases. It was determined that women, those with higher incomes, and those who have encountered an PWE have more knowledge about epilepsy. It was also observed that those with higher incomes, those who are young or young adults, those who are single, and those who have witnessed an epileptic seizure have developed more positive attitudes toward PWE.